IDENTIFIKASI CACING POLYCHAETA, Nereis sp. SEBAGAI VEKTOR WHITE SPOT SYNDROME VIRUS (WSSV) DI ALAM DAN KAJIAN UJI TANTANGNYA DI LABORATORIUM = IDENTIFICATION OF POLYCHAETE WORM, Nereis sp. AS A WHITE SPOT SYNDROME VIRUS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Polychaeteworm is an important zoobenthos in shrimp culture system. However,since there is no culture of these worm in Indonesia, so that all the worm biomass collected from their natural habitat. It raised some concerns about their safety because polychaete worm might be get infected and will realistic as a pathway for virus to attack shrimp broodstock in the hatchery. Fresh polychaete worms (1 9 wet) used as a test organisms were caught from pond area in Semat region, Jepara. The step of these experiment are identification of WSSV infection at wild polychaete worms with PCR analysis, visual, microscope and histology observation. Followed by challenge test of polychaete worm with WSSV, and WSSV infectivity study at black tiger shrimp broodstock. The results revealed that using two different PCR methods, OlE (2006) and Nugen kit, and histology analysis showing noWSSV infection in polychaete worms. However, from further experiment showing that polychaete worm challenge by WSSV have already got severely stress due to WSSV inocculum treatment, but the level of infection is still very low so that can not detect by PCR. Shrimp broodstock that have already fed with WSSV-contaminated polychaete worms for 1 week, based on clinical signs seems to get infected by WSSV, even the infectivity level is still very low. It concluded that polychaete worm can be a vector for WSSV in pond.